THE EFFECT OF MINT ESSENCE ON GASTROINTESRINAL DISORDER AFTER CESAREAN SECTION - N. fazel (Iran University of Medical Sciences, 2004)
Fatigue is one of the most common and a distressing side effect of cancer and its treatments. Fortunately, there are simple and unexpensive strategies to relieve fatigue intensity.   To determine strategies used by cancer patients to cope with fatigue during chemotherapy, a descriptive longitudinal study was conducted. Contributors were 120 cancer patients receiving chemotherapy. The principle method of data collection was a daily dairy.   The results indicated that patients used different strategies to fight with their fatigue, the most common approaches were resting (20.7%) and stop working (11.7%) and the least were doing exercises (3.3%) and walking (4.2%).   To conclude, as Findings showed that cancer patients, receiving chemotherapy have used different strategies to cope their fatigue, recommendation is made to compare the efficacy of these strategies in these patients.